Forms and Functions of Indonesian–English Code-Mixing on the YouTube Channel “Kok Bisa?”: A Digital Sociolinguistic Study - Ely Purwanti; Merry Lapasau; Samsinar Sambo; Putri Rahayu; Rifka Agustin (PT FORMOSA CENDEKIA GLOBAL, 2026)
The development of digital media has transformed societal communication patterns, including the use of code-mixing between Indonesian and English. This study aims to describe the forms and functions of code-mixing in educational YouTube content. A qualitative descriptive method and digital sociolinguistic approach were applied, as the study examines the relationship between language use and the social context of digital communication in a bilingual society. Data were collected from 20 videos uploaded to the